2008
DOI: 10.1177/0960327108094509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pesticide exposure on the human immune system

Abstract: Epidemiological evidence from Western countries indicates that the prevalence of diseases associated with alterations in the immune response, such as asthma, certain autoimmune diseases and cancer, are increasing to such an extent that it cannot be attributed to improved diagnostics alone. There is some concern that this trend could be, at least, partially attributable to new or modified patterns of exposures to chemicals, including pesticides. The purpose of this article is to review the evidence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 68 publications
1
64
0
7
Order By: Relevance
“…Moreover, bone marrow-derived immune components are continuously being renewed. Lastly, immune surveillance and responses to pathogens demand a delicate tuning [16].…”
Section: Environmental Estrogensmentioning
confidence: 99%
“…Moreover, bone marrow-derived immune components are continuously being renewed. Lastly, immune surveillance and responses to pathogens demand a delicate tuning [16].…”
Section: Environmental Estrogensmentioning
confidence: 99%
“…Studies have shown DTC induce the activation of T cells, natural killer cells and increase immunoglobulin secretion by B cells [30]. DTCs can act as haptens, which on conjugating to proteins may induce allergic hypersensitivity [31].…”
Section: Discussionmentioning
confidence: 99%
“…As a general rule, all EBDCs are characterised by low acute toxicity and short environmental persistence (1). Nevertheless, the most used compound of this group, mancozeb, has been reported as having goitrogenic (2, 3) and endocrine disrupting effects (4-6), as well as being possibly immunotoxic (7)(8)(9). In mammals, mancozeb produces several metabolic products among which the most relevant is Ethylenebis-thiourea (ETU), which is also a product of its environmental degradation (10).…”
Section: (Phomopsis Viticola) and Black Rot (Guingardia Bidwelli)mentioning
confidence: 99%